Human Immuno-deficiency Virus (HIV) infection among oral surgery patients at the University College Hospital, Ibadan, Nigeria (2003)
The human immuno-defiency virus is a world-wide epidemic and evidence abound that the infection is spreading rapidly in sub-saharan Africa with little or no control. Nosocomial trans mission of HIV in the Dental surgery has been documented. This study was undertaken to determine the prevalence of HIV among dental patients undergoing extraction at the University College Hospital, Ibadan. Three hundred patients requiring dental extraction at the dental clinic, UCH, Ibadan who consented were enrolled for the study. Blood samples from these individuals were tested for the presence of HIV antobodies using commeercially available ELISA (Monolisa Sanofi, Pasteur, France). All initially reactive samples were confirmed by a commerical Western immunoblot assay (Bio-Rad Norapath HIV kit). Aprevalence of 2.3 % (7/300) was obtained among individuals tested for this study. Four (2.8%) of the 143 males and 3 (1.9%) of 157 females were positive for HIV antibodies. All the seropositive patients except one were within the age range 20-39 years and most of them (6 out of 7) do not use condom during intercourse. More than half (57%) of the patients had more than one sexualy partner. This study shows that the risk of transmitting HIV to DHCW during treatment is also a ptential hazard in ths environment. HEnce, adequate preventive measures should be observed always.